Selective concentration for ciprofloxacin resistance in Escherichia coli grown in complex aquatic bacterial biofilms. (July 2018) - Kraupner, Nadine; Ebmeyer, Stefan; Bengtsson-Palme, Johan; Fick, Jerker; Kristiansson, Erik; Flach, Carl-Fredrik; Larsson, D.G. Joakim
Abstract: There is concern that antibiotics in the environment can select for and enrich bacteria carrying acquired antibiotic resistance genes, thus increasing the potential of those genes to emerge in a clinical context. A critical question for understanding and managing such risks is what levels of antibiotics are needed to select for resistance in complex bacterial communities. Here, we address this question by examining the phenotypic and genotypic profiles of aquatic communities exposed to ciprofloxacin, also evaluating the within-species selection of resistant E. coli in complex communities. The taxonomic composition was significantly altered at ciprofloxacin exposure concentrations down to 1 μg/L. Shotgun metagenomic analysis indicated that mobile quinolone resistance determinants ( qnrD, qnrS and qnrB ) were enriched as a direct consequence of ciprofloxacin exposure from 1 μg/L or higher. Only at 5–10 μg/L resistant E.coli increased relative to their sensitive counterparts. These resistant E. coli predominantly harbored non-transferrable, chromosomal triple mutations ( gyrA S83 L, D87N and parC S80I), which confer high-level resistance. In a controlled experimental setup such as this, we interpret effects on taxonomic composition and enrichment of mobile quinolone resistance genes as relevant indicators of risk. Hence, the lowest observed effect concentration for resistance selection in complex communities by ciprofloxacin was 1 μg/L and the corresponding no observed effect concentration 0.1 μg/L. These findings can be used to define and implement discharge or surface water limits to reduce risks for selection of antibiotic resistance in the environment. Highlights: Selective properties of ciprofloxacin were assessed in biofilms and suspensions. Bacterial communities from treated wastewater effluent were exposed. Ciprofloxacin selects for resistant E. coli at 5–10 μg/L in complex communities. Taxonomic shifts and increase in mobile quinolone resistance were found at 1 μg/L. Ciprofloxacin should not exceed 0.1 μg/L to limit risks for resistance selection.